Sacrospinosus Fixation Efectivity in Pelvic Organ Prolapse Patient: Efektivitas Fiksasi Sakrospinosus pada Penderita Prolaps Organ Panggul - Yulius Andriansyah; Amir F; Firmansyah B; Theodorus Theodorus (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract Background : Pelvic organ prolapse (POP) is a condition in which interna genitalia protrude into vagina, or even out of vagina. This occur due to weaknesses of pelvic muscle, fascia and ligaments support. Sacrospinous ligament fixation (SSF) is an ideal vaginal procedure for POP repair with 90-95% success rate. This study aims to determine the effectiveness of SSF in patients with POP at dr. Mohammad Hoesin hospital (RSMH) Palembang Method: Randomized clinical trial (RCT) was performed at RSMH Palembang from January to September 2017. There were 30 samples of pelvic organ prolapse who met the inclusion criteria. Data frequency and distribution were described in table form and the effectiveness of SSF were analyzed by Wilcoxon / paired t-test while the effectiveness ratio was analyzed by Mann Whitney / independent t-test. Data were analyzed using SPSS version 16.0. Result: There were no differences in patient characteristics (age, parity, body weight, height, and occupation) between the two treatment groups (p <0.05). There were differences of breech pain (proctalgia) before and after 1, 3, and 6 months post operation in SSF group (p <0.05), in which proctalgia was more exquisite after than before surgery. The results showed that SSF was effective in reducing urinary disorders, defecation disorders, vaginal prolapse, cystocele and rectocele, and effectively improving the quality of life of POP patient. In addition, there was a difference of proctalgia and vaginal prolapse 1, 3, and 6 months after surgery between two groups where the adverse outcome of the proctalgia was more significant in SSF group but the vaginal prolapse was more significant in the non-SSF group. There were no differences in bleeding complications (p = 1,000) and infection (p = 1,000) between the two groups. Conclusion: Sacrospinosus Fixation was effectively reduces the vaginal prolapse of pelvic organ prolapse patients. Keywords: Urinary, Defecation, Sacrospinosus Fixation, Quality of Life, Proclatgia, Rectocele, Cystocele. Abstrak Latar Belakang:. Prolapsus organ panggul (POP) merupakan keadaan dimana suatu organ genitalia turun kedalam vagina, bahkan mungkin keluar liang vagina. Hal ini terjadi dikarenakan kelemahan otot, fasia dan ligamen penyokongnya. Sacrospinous ligament fixation (SSF) adalah prosedur vaginal yang ideal untuk perbaikan POP dengan tingkat keberhasilan 90-95%. Penelitian ini bertujuan untuk mengetahui efektivitas SSF pada penderita prolaps organ panggul di rumah sakit dr. Mohammad Hoesin (RSMH) Palembang Metode: Uji klinis acak berpembanding (RCT) dilakukan di RSMH Palembang sejak bulan Januari sampai September 2017. Didapatkan sampel sebanyak 30 penderita prolaps organ panggul yang memenuhi kriteria inklusi. Frekuensi dan distribusi data dijelaskan dalam bentuk table dan efektivitas SSF dianalisis dengan uji Wilcoxon/paired t-test dan perbandingan efektivitas dianalisa dengan uji Mann Whitney/independent t-Test menggunakan SPSS versi 16.0. Hasil: Analisis statistik tidak terdapat perbedaan karakteristik pasien baik umur, paritas, berat badan, tinggi badan, dan pekerjaan antara kedua kelompok perlakuan (p< 0,05). Didapatkan bahwa SSF efektif mengurangi gangguan berkemih, gangguan defekasi, prolaps vagina, sistokel dan rektokel serta meningkatkan kualitas hidup pasien POP, namun terdapat perbedaan nyeri bokong (proktalgia) sebelum dan sesudah 1 bulan, 3 bulan dan 6 bulan operasi pada group SSF (p <0,05). dimana proktalgia lebih dirasakan setelah operasi dibandingkan sebelum operasi. Selain itu terdapat perbedaan proklatgia dan prolaps vagina 1,3 dan 6 bulan setelah operasi antar kedua group dimana proktalgia lebih dirasakan pada kelompok SSF namun prolaps vagina lebih banyak dialami oleh kelompok non SSF. Tidak terdapat perbedaan komplikasi perdarahan (p = 1,000) dan infeksi (p = 1,000) antara kedua kelompok. Simpulan: Fiksasi sakrospinosus efektif mengurangi prolaps vagina pasien prolaps organ panggul. Kata Kunci:. Berkemih, Defekasi, Fiksasi sacrospinosus, Kualitas Hidup, Nyeri Bokong, Rektokel, Sistoke